Associations between physical size and space are strongly asymmetrical - Richter, Melanie; Wühr, Peter (Technische Universität Dortmund, 2023)
The spatial–size association of response codes (SSARC) effect describes the phenomenon that left responses are faster and more accurate to small stimuli whereas right responses are faster and more accurate to large stimuli, as compared to the opposite mapping. The effect indicates associations between the mental representations of physical size and space. Importantly, the theoretical accounts of SSARC effects make different predictions about the reciprocity and/or symmetry of spatial–size associations. To investigate the reciprocity of SSARC effects, we compared compatibility effects in two verbal choice-response tasks: a size–location (typical SSARC) task and a location–size (reciprocal SSARC) task. In the size–location task, participants responded verbally to a small/large stimulus by saying “left”/“right”. In the location–size task, participants responded verbally to a left-/right-side stimulus by saying “small”/“large”. Participants completed both tasks with a compatible (small–left, large–right; left–small, right–large) and an incompatible (small–right, large–left; left–large, right–small) mapping. A regular SSARC effect emerged in the size–location task. However, no reciprocal SSARC effect emerged in the location–size task if outliers were excluded. If outliers were not excluded, small reciprocal SSARC effects occurred. Associations underlying the SSARC effect are thus strongly asymmetrical: Physical (stimulus) size can prime spatial responses much more strongly than spatial (stimulus) position can prime size-related responses. The finding of asymmetrical associations between size and space is in line with some theoretical accounts of the SSARC effect but at odds with others.
Scientific reports;13
Keywords: Human behaviour; Psychology; 150; Mensch | Verhalten; Psychologie; Reizantwort